The Liverpool Cotton Brokers Association and the crowning of King Cotton, 1811-1900: Examining the role of a private order institution in global trade - Michael Aldous; Christopher Coyle (Queen's University Centre for Economic History (QUCEH), 2020)
In the 19th century, the Liverpool Cotton Brokers Association (CBA) coordinated the dramatic growth of Liverpool's raw cotton market. This article shows how the CBA achieved this through the development of a private order institutional framework that improved information flows, introduced standardization and contracting regimes, and regulated market exchange platforms. These developments corresponded with significantly improved market coordination, which facilitated the growth of the largest raw cotton market in the world. The article's findings demonstrate and quantify the importance of nonstate actors, in creating institutions of global exchange central to the first wave of globalization.
Keywords: D03; F13; N43; N53; N74; Q17; 330; private order institutions; non-state actors; globalization; Liverpool Cotton Brokers Association